Addressing Vaccine Hesitancy Using Local Ambassadors: A Randomized Controlled Trial in Indonesia - Asad Islam; Gita Kusnadi; Jahen Rezki; Armand Sim; Giovanni van Empel; Michael Vlassopoulos; Yves Zenou (Institute of Labor Economics (IZA), 2023)
In settings where resistance and rampant misinformation against vaccines exist, the prospect of containing infectious diseases remains a challenge. Can delivery of information regarding the benefits of vaccination through personal home visits by local ambassadors increase vaccine uptake? We conduct a door-to-door randomized information campaign targeted towards COVID-19 unvaccinated individuals in rural Indonesia. We recruited ambassadors from local villages tasked to deliver information about COVID-19 vaccines and promote vaccination through one-on-one meetings, using an interpersonal behavioral change communication approach. To investigate which type of ambassador—health cadres, influential individuals, and laypersons—is the most effective, we randomly vary the type of ambassador that delivers the information at the village level. We find that the overall vaccination take-up is quite moderate and that there are no differences in vaccination outcomes across the treatment groups. These results highlight the challenge of boosting vaccine uptake in late stages of a pandemic.
Keywords: I1; I12; I18; I20; I3; 330; misinformation; health behaviors; vaccine hesitancy; Indonesia; COVID-19